2015
DOI: 10.1016/j.jtcvs.2015.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Failure to rescue and pulmonary resection for lung cancer

Abstract: Variation in hospital mortality seems to be more strongly related to rescuing patients from complications than to the occurrence of complications. This observation is significant because it redirects quality improvement and health policy initiatives to more closely examine and support system-level changes in care delivery that facilitate early detection and treatment of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The FTR rate has several potential advantages over more convention outcome metrics. While it has been repeatedly shown that center level SAE rates correlate poorly with center level mortality rates (4, 5), center level FTR rates are strongly associated with center level mortality across a wide variety of elective surgical populations (68). Moreover, relative to risk of SAE, risk of FTR is more strongly associated with potentially modifiable center level factors such as staffing patterns and infrastructure (9).…”
Section: Introductionmentioning
confidence: 99%
“…The FTR rate has several potential advantages over more convention outcome metrics. While it has been repeatedly shown that center level SAE rates correlate poorly with center level mortality rates (4, 5), center level FTR rates are strongly associated with center level mortality across a wide variety of elective surgical populations (68). Moreover, relative to risk of SAE, risk of FTR is more strongly associated with potentially modifiable center level factors such as staffing patterns and infrastructure (9).…”
Section: Introductionmentioning
confidence: 99%
“…Such gaps affect short-term outcomes, such as postoperative mortality and hospital readmission rates [7,8]. Gaps in the oncologic quality of resection may be more difficult to measure because of their delayed manifestation [9].…”
mentioning
confidence: 99%
“…FTR studies have been motivated by a surprising finding identified in numerous independent studies; specifically, investigators found that the complication rate between the best and worst hospitals differs only slightly, whereas FTR for the best centers is markedly better than the FTR of centers with poor performance [3][4][5][6][7][8]. FTR, then, appears to complement traditional approaches by focusing on an important aspect of care that has previously been a blind spot in objective quality measurement [3,[9][10][11][12][13].…”
mentioning
confidence: 99%
“…The focus in surgical studies has been on complications after an operative procedure. Some investigators have used an array of operations [7-9, 11, 12], whereas others have studied a single operation [3,14,15]. Likewise, some have examined a set of complications [7-9, 12, 14] rather than a single complication [16].…”
mentioning
confidence: 99%